Draft Progress of Selected Projects Upto 30th June, 1957 - Planning Commission (Planning Commission, 1957)
The construction and expansion programmes of the three projects, namely Durgapur Steel Project, Mysore Iron and Stool Works and Tata Iron and Stole Co. report progress broadly according to schedule. on the other hand there were some difficulties in making arrangements for Civil engineering construction on the large scale required in case of Bhilai and Rourkela Steel projects. There were some delay in Slipping, and unloading, and shortage of cement and skilled labour in case of Indian Iron and Stool Co. But it is reported that everything is being done to keep upto the original schedule.
Statistics and Surveys Division
Statistics and Surveys Division Planning Commission